The Scarecrow - Ferry, Beth; Fan, Terry; Fan, Eric (New York, NY Harper, an imprint of HarperCollinsPublishers, 2019)
All the animals know not to mess with old Scarecrow. But when a small, scared crow falls from midair, Scarecrow does the strangest thing. He saves the tiny baby crow. Soon a loving bond grows between the two unlikely friends. But is it strong enough to weather the changing of the seasons?
Keywords: Scarecrows -- Juvenile fiction; Crows -- Juvenile fiction; Friendship -- Juvenile fiction; Seasons -- Juvenile fiction; Scarecrows -- Fiction; Crows -- Fiction; Friendship -- Fiction; Seasons -- Fiction; Picture books